Genetic Structure, Function, and Evolution of Capsule Biosynthesis Loci in Vibrio parahaemolyticus - Bian, Shengzhe; Zeng, Wenhong; Li, Qiwen; Li, Yinghui; Wong, Nai-Kei; Jiang, Min; Zuo, Le; Hu, Qinghua; Li, Liqiang (Frontiers in Microbiology, 2021)
Capsule-forming extracellular polysaccharides are crucial to bacterial host colonization, invasion, immune evasion and ultimately pathogenicity. Due to warming ocean waters and human encroachment of coastal ecosystems, Vibrio parahaemolyticus has emerged as a globally important food-borne enteropathogen implicated in acute gastroenteritis, wound infections, and septic shock. Conventionally, the antigenic properties of lipopolysaccharide (LPS, O antigen) and capsular polysaccharide (CPS, K antigen) have provided a basis for serotyping V. parahaemolyticus, while disclosure of genetic elements encoding 13 O-serogroups have allowed molecular serotyping methods to be developed. However, the genetic structure of CPS loci for 71 K-serogroups has remained unidentified, limiting progress in understanding its roles in V. parahaemolyticus pathophysiology. In this study, we identified and characterized the genetic structure and their evolutionary relationship of CPS loci of 40 K-serogroups through whole genome sequencing of 443 V. parahaemolyticus strains. We found a distinct pattern of CPS gene cluster across different K-serogroups, and expanded its new right-border by identifying glpX as a key gene conserved across all serotypes. A total of 217 genes involved in CPS biosynthesis were annotated. Functional contents and genetic structure of the K-serogroups were analyzed. Based on inferences from species trees and gene trees, we proposed an evolution model of the CPS gene clusters of 40 K-serogroups. Horizontal gene transfer by recombination from other Vibrio species, gene duplication and nonsense mutations are likely to play instrumental roles in the evolution of CPS in V. parahaemolyticus. It is the first time, to the best of our knowledge, that a large-scale of CPS gene clusters of different K-serogroups in V. parahaemolyticus have been identified and characterized in evolutionary contexts. This work should help advance understanding on the variation of CPS in V. parahaemolyticus, and provide a framework for developing diagnostically relevant serotyping methods.